Households and entrepreneurship in England and Wales, 1851–1911. Issue 1 (2nd January 2021) - Smith, Harry; Bennett, Robert J.; van Lieshout, Carry; Montebruno, Piero
ABSTRACT: This article uses the British Business Census of Entrepreneurs (BBCE) to examine the relationship between the household and entrepreneurship in England and Wales between 1851 and 1911. The BBCE allows three kinds of entrepreneurial households to be identified: those where an entrepreneur employs co-resident family members in their business, those where two or more household members are partners in the same firm, and households with two or more entrepreneurs resident who are running different firms. The article traces the number of these different households across the period and examines their sector and gender breakdowns as well as their geographical distribution. The article demonstrates that these different kinds of entrepreneurial households served different purposes; co-resident family businesses were used in marginal areas where other sources of labour and capital were scarce and the incidence of such firms decreased over this period. In contrast, household partnerships and co-entrepreneurial households were used to share risk or diversify; they were found throughout England and Wales at similar levels during this period.